الخوارج ودورهم في سقوط الدولة الأموية 37 - 132هـ - عامر, محمد كاظم حسن (مجلة الجامعة العراقية, 2023)
ملخص البحث: يمثل الخوارج إحدى الحركات الثورية التي صنعت لها لباساً عقائدياً بعد خروجهم على الخليفة علي بن أبي طالب (رضي الله عنه) بعد قضية التحكيم في موقعة صفين ليتحولوا بعدها إلى مصدر قلق سياسي للخلافة…
Keywords: Kharijisme

فكر الخوارج في عهد الامام علي (عليه السلام) دراسة تاريخية - كاظم, الباحثة شذى علي (المجلة العراقية للبحوث الانسانية والاجتماعية والعلمية, 2023)
The emergence of the Kharijite sects in the Islamic nation led to the occurrence of many differences and divisions in the political, religious, social, intellectual and other aspects. These sects established…
Keywords: Kharijisme

الخوارج في الفكر الإسلامي القديم: التّأويل والتّأويل المضاد بين أهل السنة والجماعة والإباضية - تغلات, زهير (ندوة المدينة (الدورة الثالثة): الإنسان والتأويل, 2023)
Keywords: Kharijisme

"The Caliph Calls You to the Book of God": Writing to Rebels in the Early Islamic Period - Hagemann, Hannah-Lena (The Medieval Globe, 2023)
This article examines rhetorical strategies in letters from rulers to rebels as part of a complex system of early Islamic conflict resolution. It offers a historical, historiographical, and literary analysis of two case studies (late seventh and early ninth century), locating them within a broader discourse of political authority and opposition that was couched in the covenantal lexicon of the Qurʾan and also included the safe-conduct (amān) and oath of allegiance (bayʿa). Beyond the two main case studies, the article suggests a common template of letters to rebels that grants insight into the political culture of the early Islamic period.
Keywords: Kharijisme

اتجاهات الخوارج في التفسير في العصر الحديث - المزروع, هند بنت محمد عبد الله (مجلة الدراسات العربية, 2023)
This research deals with the trends of the Kharijites in interpretation in the modern era. The research aims to reveal the origins of the Kharijites, their branches, their pioneers, their fundamentals, their approach, their general characteristics, and their most important deviations in interpretation, and to know the reasons behind the lack of production of the Kharijites in exegesis. The research reached a number of results, including that the Ibadis still carry some of the fundamentals of the ancient Kharijites. The research revealed the lack of discipline in the way of the Kharijites in interpretation. It is a mixture of opinion and reasoning with the words of the predecessors and mental citations.
Keywords: Kharijisme